Programa de apoio aos dirigentes municipais de educação : articulações e interpretações - Menezes, Pamela Jordana de (2019)
This thesis paper is the result of an investigation which is inscribed in the Research Line Educational Public Policies in the Graduate Program in Education of the Federal University of Mato Grosso, campus of Rondonópolis, having as theme the Program of Support to the Municipal Educational Directors (PRADIME). The aim was to analyze the meaning attributed to the policy of management, constituted as Program of Support to the Municipal Educational Directors based on the policy texts which materialize it and, in addition, its relation with the meanings constructed in the texts of the policy of preparation training for the municipal directors, instituted by UFMT, in the form of Lato Sensu Post-graduate. In order to reach the proposed aim, we opted for the method denominated approach of policy cycle, developed by Stephen J. Ball and his collaborators. Such method proposes an analysis of all the history of constitution of a public policy, establishing three contexts of analysis: influence, production of text and of the practice. The study was carried out considering that the cited contexts are interrelated and do not constitute themselves in linear stages, presenting each one, arenas, groups of interests and conflict. Is possible to highlight, eventually, that the main objective proposed in the policy of PRADIME is to improve the preparation training of the municipal directors and the tech staff of the scenario of the Education Municipal Secretaries, to act in the areas of educational and school management of the teaching systems, in order to contribute to the improvement and the attainment of the excellence in the quality, as well as so that these municipal actors exercise their strategic role in the articulation of educational policies in the corresponding designations, which is in line with the objectives proposed by policy of preparation training, in the post-graduate level, instituted by UFMT.